Progressing on-court rehabilitation after injury: the control-chaos continuum adapted to basketball - Taberner, M.; Spencer, N.; Murphy, B.; Antflick, J.; Cohen, D. D. (Journal of Orthopaedic & Sports Physical Therapy, 2023)
BACKGROUND: Sport-specific training is an integral component of returning to sport following injury. Frameworks designed to guide sport-specific rehabilitation need to integrate and adapt to the specific context of elite sport. The control-chaos continuum (CCC) is a flexible framework originally designed for on-pitch rehabilitation in elite football (soccer). The concepts underpinning the CCC transfer to other elite sport rehabilitation environments.